Rice leaf heterogeneity in chlorophyll fluorescence parameters under short-term osmotic stress - J. Z. Li; Y. P. Chen; K. Q. Teng; L. Z. Qin; Y. X. Du; J. Zhang; Q. Z. Zhao (Biologia Plantarum, 2015)
The effects of short-term osmotic stress [a polyethylene glycol (PEG) treatment] on photosystem II (PS II) of upland and lowland rice seedlings were investigated using chlorophyll (Chl) fluorescence imaging. Spatial heterogeneity in the top fully expanded leaf for all Chl fluorescence parameters was found under stress conditions. After exposure to PEG, a decrease in the effective quantum yield of PS II photochemistry (φPS II) and photochemical quenching (qP), and an increase in non-photochemical quenching (NPQ) proceeded from the upper section to the base of the leaf. The most sensitive position in the leaf was different between the two ecotypes. Chl fluorescence parameters, net photosynthetic rates (PN), and stomatal conductance (gs) were more sensitive to the PEG stress in upland rice than in lowland rice. These results also indicate different leaf anatomy and development in the two rice ecotypes. Additionally, the findings suggest a more rapid stress response in upland rice.